Threats to Inland Water Ecosystems in the Lake Victoria Basin – A Review in Relation To Water Resources Management Planning - Odenyo , Victor A. O.; Verdonck, Julien (African Journal of Education,Science and Technology (AJEST), 2015)
The Lake Victoria Basin (LVB) spreads over the 5 countries of the East African Community: Burundi, Kenya, Rwanda, Tanzania and Uganda. Inland water systems in the LVB include habitats such as lakes and rivers, marshes, swamps and floodplains, small streams, ponds, and cave waters, and have a temporal dimension – varying from perennial to ephemeral – and a dynamic dimension, including flowing systems, standing waters, and systems with at times large seasonal fluctuations in water depth. The ecosystem represents approximately 11% of the LVB, excluding Lake Victoria itself. The study aimed to assess the major threats to the inland water ecosystems of the basin, focused on the threats to the ecosystem vis-à-vis their future contribution to the quantity and quality of water in the basin as it was part of a preliminary study leading to the formulation of a water resource management plan for the LVB. It involved mainly document review and limited field observations. The major current threats were found to be Forest clearing, Agricultural expansion, and Urban and industrial pollution, all driven by a rapidly expanding, poor population. The study concluded that poverty was the defining driver, and that reducing environmental degradation requires a global integrated approach targeting poverty: it is clear that any effort in reducing ecosystems degradation may be nullified in the medium-term if it is not accompanied by a reduction in the growth of the population using agricultural land. This could be achieved by a global reduction in population growth rate and/or by providing alternative sources of livelihoods (mainly off-farms activities) to the population. Without this the quality of the basin‘s waters and livelihoods will be in jeopardy.